Maternal and neonatal complications of pregnant women with bipolar disorder: a systematic review and meta-analysisResearch in context - Damien Etchecopar-Etchart; Masoud Rahmati; Dong Keon Yon; Lee Smith; Laurent Boyer; Guillaume Fond (EClinicalMedicine)
Summary: Background: Confidence in pregnancy outcome data for women with bipolar disorder is compromised by small cohort sizes. However, comprehensive national data have been published over the last decade, but no quantitative synthesis has been established to determine the factors associated with complications in these women. Our goal is to summarise the evidence of population-based data on obstetric complications and neonatal outcomes in women with bipolar disorder compared to women without bipolar disorder. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines, a comprehensive search was conducted of PubMed/MEDLINE, Embase, PsycINFO, Web of Science, and Google Scholar from inception to September 26th, 2024. Thirty-six outcomes were extracted from eligible articles for consideration. The study protocol was registered on PROSPERO (CRD42023369031). Findings: Fourteen population-based retrospective cohort studies from six high-income countries (Australia, Canada, Hong-Kong, Sweden, Taiwan, and USA) involving 47,954 women with bipolar disorder and their newborns compared to 11,896,577 women without bipolar disorder, published between 2005 and 2024, were identified. During pregnancy, women with bipolar disorders seemed to exhibit an increased risk of gestational diabetes OR = 1.46, (95% Confidence Interval [1.06–2.03]; I2 = 87%), gestational hypertension OR = 1.19 (95% CI [1.02–1.40]; I2 = 41%), antepartum haemorrhage OR = 2.02 (95% CI [1.30–3.13]; I2 = 67%), and pre-eclampsia or eclampsia OR = 1.20 (95% CI [1.05–1.36]; I2 = 67%). At delivery, women with bipolar disorder were observed to face a higher risk of caesarean section OR = 1.35 (95% CI [1.26–1.45]; I2 = 56%), and postpartum haemorrhage OR = 1.39 (95% CI [1.20–1.62]; I2 = 0%). Their newborns also appear to be at high risks of very prematurity OR = 1.84 (95% CI [1.32–2.57]; I2 = 74%), infant death OR = 1.77 (95% CI [1.01–3.13]; I2 = 41%), low birth weight OR = 1.54 (95% CI [1.19–1.99]; I2 = 70%), preterm birth OR = 1.49 (95% CI [1.29–1.72]; I2 = 87%), small for gestational age OR = 1.28 (95% CI [1.14–1.45]; I2 = 57%), and congenital malformations OR = 1.29 (95% CI [1.09–1.53]; I2 = 42%). According to the AMSTAR 2 tool, these results correspond to moderate-quality evidence. Interpretation: Despite substantial heterogeneity observed, our findings suggest the presence of a broad spectrum of complications that may affect both pregnant women with bipolar disorder and their newborns. These results can serve as a basis for the development of guidelines for the prevention and management of these complications. We need additional data from other countries, particularly from low-to-moderate income countries. Funding: The ‘Jeunes Espoirs de la Psychiatrie’ (Young Hopes of Psychiatry) doctoral programme is supported by the Fondamental Foundation and sponsored by the Bettencourt Schueller Foundation.